Svenska viltarters inverkan på foderproduktion - Åberg, Malin (SLU/Dept. of Animal Nutrition and Management (until 231231), 2017)
Abstract Game related crop damage is a complex issue depending on several different factors and the current knowledge of how ungulate and crop damage are linked is scarce. This study aims to view if it is possible to connect ungulate densities of a study area with a new method for estimating grazing pressure and damage. If so, the current methodology could be used as a template for future estimation on ungulate impact, both concerning actual yield losses and economic losses. Vegetation height and damaged area was measured on 37 fields within the county of Södermanland. The farmers for each of the fields were sent questionnaires concerning farming, game and hunting. The results from the survey were analysed separately and compared with a survey conducted in 2014 where the same questions were sent to other Swedish farmers. Farmers in the current study experienced a higher mean damage and higher risk of economic losses due to game damage, than the Swedish average. A higher proportion of the farmers in the current study found the damage and the grazing pressure of the crops as unacceptable. The farmers which saw the crop damage as unacceptable were significantly more negative towards occurrence of fallow deer and wild boars. Farmers with fields in areas with high density of fallow deer were more likely to be involved in conflicts concerning game management. There was a significantly negative connection between fallow deer density of the field areas and vegetation height, which probably would result in reduced harvest yields of forage. The methodology of the study could be used to estimate grazing pressure, but could be improved by adding protected areas for comparison, as well as nutritional measurements and economic impact estimates.